Visual Scaffolding and Intensive Reading Strategies Based on Gender - Asti Veto Mortini; Aswadi Jaya (Esteem Journal of English Education Study Programme, 2021)
The objectives of  this study are to find out whether or not;  1) there is a significant increase in students’ reading comprehension achievement based on after they are taught by using visual scaffolding strategy and intensive reading strategy and those who are not. 2) there is a significant contribution of visual scaffolding strategy and intensive reading strategy towards reading comprehension achievement  of the high, average, and low achievers? This reserach used factorial experimental designs.  These designs are essentially modifications of either the posttest-only control group or pretest-posttest control group designs. The sample was the students of PGRI University of Palembang. Two classes were chosen in which first class was experimental with male students was applied and the second was the second experiemnetal group trained by intensive reading strategy with the female students. The results showed that First, Visual scaffolding and Intensive Learning Strategy technique affected the students’ reading achievement of PGRI University. The result of t independent test was the mean of experiment group higher than mean of control group. It could be concluded, experiment group and control group were significantly difference and the visual scaffolding and Intensive Learning Strategy technique was effectively to use in improving students’ reading achievement.  The Second, there was an interaction effect of visual scaffolding and intensive learning strategy technique and students’ learning achievement toward the students’ reading achievement.